HISTORICAL AND PEDAGOGICAL PREDICTORS OF INNOVATION ACTIVITIES IN EDUCATION - Kozak, Liudmyla V. (Educological discourse, 2014)
The article examines the historical and pedagogical prerequisites of development and innovation in education. The analyses of historical and innovative educational ideas that are relevant in the present conditions modernize our education.